Profitability and Efficiency of Poultry Business in Ogun State, Nigeria - Adewunmi Idowu; Deborah Olude; Mojisola Kehinde; Maria Ogunnaike; Christopher Ologbon; Olumayowa Oyebanjo (International Journal of Small and Medium Enterprises and Business Sustainability, 2024)
This study investigates the effect of poultry farm efficiency on its profitability level in ogun state, Nigeria. The study drew a sample of 300 poultry farms through a multistage sampling technique from four agricultural zones in Ogun State and data were analysed using parametric frontier approach, budgetary analysis, profitability indices and Tobit model.Results indicates that mean age, years of formal education and poultry farm experience were 47.3 years, 17 years, and 7.9 years respectively. The mean efficiency estimates for technical, allocative, and economic efficiency were 0.95, 0.12 and 0.11 respectively while age and poultry farms experience significantly reduced cost inefficiency. The average gross margin and net income were found to be 76,470.92 (USD 250.07) and 76,176.65 (USD 249.11) while average farm profitability index (0.29), rate of return on investment (43.22), rate of return on variable cost (143.78) and operating (0.71) indicated that poultry business is profitable in Ogun State.Increase in technical efficiency significantly increase the tendency of poultry farms making more profit.Implications were drawn for increased production scale and cooperate establishment of feed mill by poultry farmers